Effects of Health Education on Food Safety Attitudes and Behavioral Intentions Among Pregnant Mothers in Rivers State, Nigeria - Ibara, Augustina Ngozi; Elechi, Comfort Emma (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This study investigated the effects of health education on attitudes and behavioural intentions towards food safety cognitions among pregnant mothers in Rivers State. A pre-test and post-test design was adopted with a population which consisted of 1,838,789 pregnant mothers attending primary healthcare institutions in Rivers State. A sample size of 270 was selected using a multistage sampling procedure. Data was collected using a structured test instrument with a reliability index of 0.78. Data collected were analyzed with the aid of the Statistical Product for Service Solution (SPSS V-23) using mean, standard deviation (SD) and One-Way Analysis of Covariance (ANCOVA) at 0.05 level of significance. The findings of the study revealed that health education had a positive effect on attitude towards food safety with a total mean difference of 1.13, and on behavioural intention with a total mean difference of 1.09. The result of the ANCOVA showed that the intervention had a significant effect [F(1,49) = 2.15, p<0.05] on attitude towards food safety. It was concluded that health education is an effective strategy to influence pregnant mothers' food safety attitudes and behavioural intention, which is necessary to prevent them and their babies from food-borne diseases or food poisoning. It was recommended that every pregnant woman must ensure she closely monitors the food preparation process to ensure food hygiene practices are fully observed. Food monitoring officials should come-up with or set official regulations as well as food hygiene standards for pregnant mothers and ensure such regulations are enforced. The government should provide hand washing and other food safety materials to encourage the women with good intentions to practice food safety to do so with confidence.